Rethinking the Algiers Charter in contemporary film production in Zimbabwe: conversations with film producers - Mkwendi, Chengeto Pauline (Midlands State University, 2017)
This study sets motion for systematic academic investigations on the Algiers Charter of 1975 and film production in Zimbabwe and Africa at large. The charter stipulates that filmmakers should be committed to the development of an ‘African’ cinema, radically different from previous cinematic representations of Africa by the Western world, rejecting commercial influence. Despite the centrality of the charter in film production, systematic academic studies on the phenomenon in the Zimbabwean context are scarce. Theoretically informed by Third Cinema theory and utilizing a qualitative research approach, the study investigates the feasibility and relevance of the Algiers charter in the context of film production in Zimbabwe. In-depth semi structured interviews were conducted with five purposively selected film producers drawn from some of Zimbabwe’s major cities: Harare, Masvingo and Gweru. From the data obtained, the study comes to the conclusion that the Algiers charter is hardly known by Zimbabwean film makers despite its importance. Moreover, while some film makers might be profit oriented, an ever bleeding Zimbabwean economy makes it impossible for the film makers to make financial profits. Finally, the study contends that Zimbabwe’s film industry, has failed to radically divorce itself from the western gaze of the African scenario.